Integrasi Pendidikan Karakter dalam Manajemen Peserta Didik di MI Muhammadiyah Pk Kartasura - Zaenudin, M; Baidi, Baidi; Imam Sukardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the integration of character education into student management at MI Muhammadiyah PK Kartasura and to identify forms of multi-stakeholder synergy in supporting student character development. The research method used was field research with a qualitative descriptive approach. Data collection techniques were conducted through semi-structured interviews, observation, and documentation. The research subjects were the vice principal for student affairs, classroom teachers, and educational staff. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. Their validity was tested using technical triangulation and source triangulation. The results indicate that the integration of character education is implemented in a structured manner through the integration of character values ​​into the formal curriculum, daily habits (hidden curriculum), teacher role models, a reward and punishment system, and the active involvement of parents and the community through collaborative programs. The coaching process is carried out systematically through the socialization of rules, behavior monitoring, gradual mentoring, and periodic evaluation. The conclusion of this study confirms that the school's character-based student management is effective because it is supported by a well-planned system, a consistent school culture, and multi-stakeholder synergy, despite facing the challenges of the digital era and inconsistent family supervision. Keywords: Character Education, Student Management, School Culture, Multi-stakeholder Synergy